Improving Prosthetic Hernioplasty Techniques in The Surgical Management of Anterior Abdominal Wall Hernias - M.M, Dusiyarov; S.T, Khujabaev; M.S, Saidov; U.A, Sherbekov; K.U, Sherkulov; O.T, Yunusov; G.F, Yunusova (Journal of Neonatal Surgery, 2025)
This article presents the findings of a comparative clinical study evaluating the efficacy of different prosthetic hernioplasty techniques for anterior abdominal wall hernias. A total of 114 patients were enrolled and allocated to two cohorts: the first underwent the conventional onlay technique, while the second received an enhanced sublay repair with retromuscular mesh placement. The results demonstrate that sublay hernioplasty is associated with a significantly lower incidence of postoperative complications (seroma, surgical-site infection), a shorter length of hospital stay, and a trend toward reduced hernia recurrence. The proposed technique can therefore be recommended as an effective alternative to traditional onlay hernioplasty